2017
DOI: 10.5194/isprs-archives-xlii-2-w5-561-2017
|View full text |Cite
|
Sign up to set email alerts
|

Modern Processing Capabilities of Analog Data From Documentation of the Great Omayyad Mosque in Aleppo, Syria, Damaged in Civil War

Abstract: Commission VI, WG VI/4KEY WORDS: Syria, documentation, Aleppo, Great Omayyad mosque, analogue photos, IBMR ABSTRACT:In 1999, a big project for the documentation of the Great Omayyad mosque in Aleppo / Syria under UNESCO was conducted. By end of the last century, still analogue cameras were still being used, like the UMK Zeiss, RolleiMetric System. Digital cameras and digital automatic data processing were just starting to be on the rise and laser scanning was not relevant. In this situation, photogrammetrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Statistical values of set of differences are presented, see Tab. 4 Table 5. RMSE values of check points measured by distinct point measurement in Agisoft PhotoScan compared to the coordinates given by CDW.…”
Section: Accuracy Checking On Check Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical values of set of differences are presented, see Tab. 4 Table 5. RMSE values of check points measured by distinct point measurement in Agisoft PhotoScan compared to the coordinates given by CDW.…”
Section: Accuracy Checking On Check Pointsmentioning
confidence: 99%
“…In literature, Agisoft PhotoScan prevails as a photogrammetric software for processing analogue images. Agisoft PhotoScan was used also by [3] to create 3D model of historic buildings, by [4] to process analogue images captured by RolleiMetric camera and UMK camera of Omayyad mosque, by [5] to analyse historic changes of a glacier, by [6] to process archival images captured by Hasselblad H5D-60 of chosen archeological area, by [7] to process analogue non-metric images and by [8] to process analogue aerial images to create DEM and orthophoto. The open-source MicMac was used for processing analogue images by [9].…”
Section: Introductionmentioning
confidence: 99%
“…The basic 3D output was a dense point cloud of the main facade of the "Post Office Palace". Since the point cloud can be deformed [7], its analysis was performed. The quality of point clouds can be estimated by a comparison with a reference base.…”
Section: D Outputsmentioning
confidence: 99%
“…Historical objects may be e.g. buildings [7][8][9], sculptures, paintings [10], archaeological sites [11,12], natural sites [13], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Processing of analog photogrammetric negatives using current methods brings new challenges and possibilities, for example, creation of a 3D model from archival images which enables comparison of historical state and current state of cultural heritage objects (Pavelka, 2017). Studies have shown that processing of analog images using current methods has huge potential in cultural heritage (Maiwald, 2017;Rodríguez Miranda, 2017).…”
Section: Introductionmentioning
confidence: 99%